Analisis Penerapan Transaksi Non Tunai Dalam Pengelolaan Keuangan Daerah Pada Sekretariat DPRD Provinsi Sumatera Barat - Khairun Nisa Afdal; Shopan Shopian (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to find out how non-cash transactions are implemented in regional financial management at the DPRD Secretariat of West Sumatra Province, to find out what obstacles arise in the implementation of non-cash transactions in regional financial management at the DPRD Secretariat of West Sumatra Province and what are the efforts to overcome the obstacles that arise on the application of non-cash transactions in regional financial management at the DPRD Secretariat of West Sumatra Province. This type of research is descriptive qualitative, the data comes from several things, namely in the form of words and actions. The rest is additional data such as documents and others. To complete the research data, two data sources are needed, namely primary data sources and secondary data sources. The analytical method used in this study is a qualitative descriptive method, namely collecting data related to the problem to be studied so that it can be described descriptively, qualitatively and comprehensively, namely describing the prevailing reality and still having something to do with applicable legal aspects. The results of the observations presented by the author use closed questions through interviews with several trusted sources who work at the Secretariat of the DPRD of West Sumatra Province. The results of the study found that the implementation of non-cash transactions carried out by the West Sumatra Provincial DPRD Secretariat was smooth and theoretical, but not all procedures were the same because in a company there were different parties and different functions together. Procedures related to the non-cash implementation system at the DPRD Secretariat of West Sumatra Province have several obstacles such as the smart city internet network that is used is still inadequate, the lack of socialization from the regional financial manager and the nagari bank regarding the non-cash implementation system, which results in a lack of understanding from related parties regarding the system This.